CD69 expression on Treg cells prevents chronic heart damage after myocardial infarction. (10th June 2022) - Blanco Dominguez, R; Martin-Aguado, L; De La Fuente, H; Rodriguez, C; Jimenez-Alejandre, R; Rodriguez-Arabaolaza, I; Garcia-Guimaraes, MM; Vera, A; Cuesta, J; Cecconi, A; Alfonso, F; Sanchez-Madrid, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministerio de Ciencia e Innovación (MCIN), through the Carlos III Institute of Health (ISCIII)-Fondo de Investigación Sanitaria (PI19/00545) Background: Increasing evidences advocate for an important function of T cells in controlling immune homeostasis and pathogenesis after myocardial infarction (MI), although the molecular mechanisms remain elusive. Result and Methods: In this study, a broad analysis of immune markers in 283 patients show a significant CD69 overexpression on Treg cells after MI. Our results in mice demonstrate that CD69 expression on Treg cells increases survival after left-anterior-descending coronary artery (LAD)-ligation. Cd69-/- mice develop strong IL17A+ gdT cell responses after ischemia that increase myocardial inflammation and, consequently, worsen cardiac function. CD69+ Treg cells induce apoptosis and decrease IL-17A production in gdT cells by a CD39-dependent mechanism. Adoptive transfer of CD69+ Treg cells to Cd69-/- mice after LAD-ligation reduces IL17A+ gdT cell recruitment increasing survival. Consistently, clinical data from two independent cohorts of patients indicate that increased CD69 expression in peripheral blood cells after acute MI is associated with a lower risk of re-hospitalization for chronic heart failure (CHF) after 2.5 years of follow-up. This result remained significant after adjustment for age, sex and traditional cardiac damage biomarkers (OR 0.929, 95% CI, 0.838-0.980; p<0.0409). Conclusion: Our data highlight CD69 expression on T cells as a therapeutic and prognostic target to prevent CHF after MI.